La langue de l’étranger: Јазикот на странецот - Derrida, Jacques; Angelovska, Despina (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jacques Derrida | Жак Дерида Title (French): La langue de l’étranger Title (Macedonian): Јазикот на странецот Translated by (French to Macedonian): Despina Angelovska | Деспина Ангеловска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 189-221 Page Count: 33 Citation (French): Jacques Derrida, “La langue de l’étranger,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 189-221. Citation (Macedonian): Жак Дерида, „Јазикот на странецот“, превод од француски Деспина Ангеловска, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 189-221.